TAMI-33. AURKA INHIBITION REPROGRAMS METABOLISM AND IS SYNTHETICALLY LETHAL WITH FATTY ACID OXIDATION INHIBITION IN GLIOBLASTOMA. (9th November 2020) - Nguyen, Trang; Shang, Enyuan; Shu, Chang; Mela, Angeliki; Humala, Nelson; Mahajan, Aayushi; Quinzii, Catarina; Westhoff, Mike-Andrew; Karpel-Massler, Georg; Bruce, Jeffrey; Canoll, Peter; Siegelin, Markus
Abstract: Aurora kinase A (AURKA) has emerged as a viable drug target for glioblastoma (GBM), the most common malignant primary brain tumor in adults with a life expectancy of 12-15 months. However, resistance to therapy remains a critical issue, which partially may be driven by reprogramming of metabolism. By integration of transcriptome, chromatin immunoprecipitation with sequencing (CHIP-seq.), assay for transposase-accessible chromatin with sequencing (ATAC-seq.), proteomic and metabolite screening followed by carbon tracing (U- 13 C-Glucose, U- 13 C-Glutamine and U- 13 C-Palmitic acid) and extracellular flux analysis we provided evidence that genetic (shRNA and CRISPR/Cas9) and pharmacological (Alisertib) AURKA inhibition elicited substantial metabolic reprogramming mediated in part by inhibition of MYC targets and concomitant activation of PPARA (e.g. PGC1A) signaling. While glycolysis was suppressed by AURKA inhibition, we noted a compensatory increase in oxygen consumption rate (OCR) fueled by fatty acid oxidation (FAO). Whereas interference with AURKA elicited a suppression of c-Myc, we detected an upregulation of PGC1A, a master regulator of oxidative metabolism, upon AURKA inhibition. Silencing of PGC1A reversed the increase in OCR and sensitized GBM cells to AURKA inhibition mediated reduction in cellular viability. CHIP experiments confirmed binding of c-Myc to the promoter region of PGC1A, which is abrogated by AURKA inhibition and in turn unleashed PGC1A expression. ATAC-seq. confirmed higher accessibility of the MYC binding region within the PGC1A promoter. Forced expression of c-Myc blocked AURKA inhibition mediated increase of PGC1A, suggesting that c-Myc acted as a repressor. To interfere with this oxidative metabolic reprogramming, we combined AURKA inhibitors with blockers of FAO (etomoxir), which elicited substantial synergistic growth inhibition and extension of overall survival in orthotopic patient derived xenografts of GBM in mice without induction of toxicity in normal tissue. Taken together, these data support that simultaneous targeting of oxidative metabolism and AURKA inhibition might be a potential novel therapy against GBM.